Cracks in refractory concrete: Transgranular or intergranular? - Christian Jung; Katja Schladitz; Claudia Redenbach; Anna Nowacka; Florentine Domrös; Michael Godehardt; Jana Hubálková (e-Journal of Nondestructive Testing)
We examine refractory concrete samples imaged in situ while undergoing compression. We suggest a method for quantifying the degree of transgranular cracking based on segmenting the aggregate and the crack systems in the computed tomography images. For comparing, validating, and training crack segmentation methods, semi-synthetic images with simulated crack structures have been proven to be very useful. Here, we extend our crack model to interact with the aggregates similarly as observed in the real samples. This in turn, opens new opportunities to train models not only segmenting but analyzing at the same time.